Systematic Literature Review (SLR) : Pengaruh Model SQ3R dalam Meningkatkan Keterampilan Membaca Pemahaman Siswa - Yusuf Ginanjar; Budi Febriyanto; Pipik Asteka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the effect of the SQ3R (Survey, Question, Read, Recite, Review) learning model on improving elementary school students’ reading comprehension skills through a Systematic Literature Review (SLR) approach. The SLR method was applied by analyzing relevant scientific articles from both national and international publications. The findings indicate that the implementation of the SQ3R model consistently provides positive impacts on students’ reading comprehension skills. SQ3R has been proven to enhance focus, active engagement, and retention of reading materials. Moreover, the model also increases students’ motivation and interest in reading, which in turn contributes to better learning outcomes. Therefore, the SQ3R model can be recommended as an effective instructional strategy to support reading literacy development in elementary schools.